Las coníferas de la Reserva de la Biosfera "La Michilía", Durango, México - Rentería-Arrieta, Laura I.; García-Arévalo, Abel (Instituto de Ecología, A.C., 2016)
This study presents the results of a taxonomic review of the conifers found in the La Michilía Biosphere Reserve in southeastern Durango, México. Two families with 13 taxa, including infraspecific levels, were identified.  The Cupressaceae family is represented by the genus Juniperus with two species and one variety and the genus Cupressus, with one species. The Pinaceae family is represented by Pinus with nine species and one variety, and one species of Pseudotsuga. A dichotomic key for species identification is included, as well as descriptions, geographical distribution, and references to the specimens examined.